Long-Term Variations of Air Temperature, SST, Surface Atmospheric Pressure, Surface Salinity and Wind Speed in the Aegean Sea - TUKENMEZ, EMRE; ALTIOK, HUSNE (Mediterranean Marine Science, 2022)
In this study, temporal and spatial trends of sea surface temperature (SST), wind speed, air temperature, sea surface salinity (SSS), sea-level pressure (SLP), and SST-based upwelling index are examined and compared with data from previous studies. Analyses of these parameters are performed for five critical locations that best illustrate the characteristic meteorological and oceanographic structures of the Aegean Sea. Upwelling index calculations are conducted with respect to latitude in order to reveal variations and detect upwelling strength easily. Long-term variations of all parameters are investigated using long-term ECMWF ERA-Interim data covering the period from 1979 to 2018; moreover, the Copernicus Marine Environment Monitoring Service (Global SSS/SSD L4) is used to obtain SSS data that cover the period of 2000-2015. Linear trend and Mann-Kendall tests are applied to identify tendencies and long-term variability. Monthly-average SST and air temperature data exhibit rising trends over the past 40 years. The results also reveal a decreasing trend in wind speed and SLP over the Aegean Sea. It is hard to determine, however, whether the current warming trend is a natural reaction of Earth or not.